# Given f(x) = 8x -2 and g(x) = 2x – 3, find f – gPlease help me solve this problem

*print*Print*list*Cite

Student Comments

atyourservice | Student

Given f(x) = 8x -2 and g(x) = 2x – 3, find f – g

the g's are going to become the opposite sign (combine the equations)

f(x) - g(x) = 8x -2 - (2x – 3)

f(x) - g(x) = 8x -2 - 2x + 3

combine like terms:

f(x) - g(x) = 8x - 2x + 3 - 2

6x + 1

revolution | Student

f(x)= 8x-2 and g(x)= 2x-3

Given these information, we need to find f(x)-g(x). So:

f(x)-g(x)= 8x-2-(2x-3)

= 8x-2-2x+3

= 6x+1

giorgiana1976 | Student

f(x)-g(x)=(8x-2)-(2x-3)

Opening the paranthesis and grouping the terms with x together and the free terms together, the result will be:

f(x)-g(x)=8x-2-2x-(-3)=(8x-2x)+(-2+3)=6x+1